Solid Clear Cell Thymoma Associated with Hydropericardium in a Labrador Retriever - Alves-Sobrinho, Ana Vitória; Alves-Ribeiro, Bruna Samara; Silva, Lizandra Fernandes da; Amaral, Andréia Vitor Couto do; Ferraz, Henrique Trevizoli; Lopes, Dyomar Toledo; Saturnino, Klaus Casaro; Ramos, Dirceu Guilherme de Souza (Acta Scientiae Veterinariae, 2024)
Background: Thymoma is an uncommon neoplasm of thymic cells that is mostly benign and limited to the mediastinum region. Despite their sporadic occurrence in animals, thymomas are the tumors that most affect the anterior mediastinum of dogs. Reports of thymomas are scarce, however, despite their sporadic occurrence in animals, thymomas are the tumors that most affect the anterior mediastinum of dogs. This study reports a benign solid clear cell thymoma associated with hydropericardium as the cause of death in a Labrador retriever. Case: One bitch presented with a history of hematemesis and hematochezia, obesity, dyspnea, bradycardia, anemia, neutrophilia, and increased liver enzymes and urea and creatinine metabolites. The hospitalization was carried out to carry out clinical examinations, but the patient died hours after admission. Necropsy revealed a pericardial sac that was severely distended with fluid, indicating the presence of hydropericardium. A firm rounded mass was observed in the mediastinum. Multiple organ fragments, nodules, and mediastinal mass were collected for microscopic evaluation. The mediastinal mass consisted mainly of solid neoplastic tissue of an epithelioid nature and lymphocytes. Other organs were normal. Lymphoid follicles and Hassall bodies were also observed, and the definitive diagnosis of benign solid clear cell thymoma associated with hydropericardium was confirmed. Despite clinical efforts and the availability investigative resources, the definitive diagnosis was only possible by necropsy due to the rapid evolution to death. The results were conclusive for the definitive diagnosis of benign solid clear cell thymoma associated with hydropericardium as the cause of death. Discussion: Compared to other neoplasms, thymoma is relatively rare. In dogs, there are few reports of proven true thymomas, most of which are benign and do not metastasize. The morphological appearance of canine thymomas, as well as size and weight, is substantially diverse. In agreement with the present report, findings in the literature report staining of thymic epithelial tumors in varying shades of pink to yellowish white, with additional sections of beige, brown, white, and red. Most canine thymomas have cysts filled with serous or serosanguineous fluid, which we also observed in this case. The solid cellular arrangement belongs to predominantly epithelial thymomas, which can also show other cellular patterns, such as trabecular, cribriform, spiral or rosette-shaped. An uncommon epithelial variant, however, is the clear cell thymoma. In this type of tumor, large round epithelial cells are visible with abundant clear cytoplasm, variably indistinct cytoplasmic margins, and often containing a single prominent nucleolus, as depicted in the present report. Hassall corpuscles are considered useful diagnostic features, as they recapitulate the medullary portion of the normal thymus. Benign thymomas can lead to death due to compression of adjacent structures. The diagnosis of thymoma during the initial phase of the disease is extremely difficult, and ultrasonography and radiographic examinations are useful in detecting cranial mediastinal tumors. In this case, the tumor mass may have caused cardiac tamponade, thereby affecting systemic circulation, especially of the precardium, thus increasing hydrostatic pressure and resulting in fatal hydropericardium, before a possible diagnosis. Keywords: canine, epithelial, Hassall’s corpuscles, histopathology, necropsy, neoplasms, thymus, tumor.